APLIKASI PENGAWET ALAMI BUAH KECOMBRANG (Nicolaia speciosa) PADA NUGGET AYAM - Rifda Naufalin; Erminawati Erminawati; Herastuti Herastuti (JURNAL AGROTEKNOLOGI, 2013)
Kecombrang (Nicolaia speciosa Horan) is one of plant tree species, contains active compounds such as polyphenols, alkaloids, flavonoids, steroids, saponins, and essential oils which exhibit antimicrobial and antioxidant activity. This research was aimed to study effect of form and concentration of Kecombrang fruit extract to chemical characteristics, microbial characteristics and sensoric characteristics in chicken nugget. The research used Randomized Block Design (RBD) with 9 treatment combinations and conducted in triplicates. The treatments tested were form of Kecombrang fruit extracts; extract, suspension, nanoencapsulan-powder; and the Kecombrang fruit extract concentrations: 1% 2% and 3%). Result of the research showed that nanoencapsulan powder of Kecombrang fruit successed to extend the chicken nugget self life, such as: to inhibit microbe growing. Nanoencapsulan-powder of Kecombrang fruit extract at concentration of 3% was more effective in reducing total bacteria, total plate-count and total mold-yeast-count, and lowering Formol-value.Keywords: nanoencapsulan powder of Kecombrang fruit, chicken nugget